An early strength shrinkage reducing admixture for prefabricated pipe segments and its preparation method and application

By using early -intensive reduction doping materials, the problems of low early intensity of the prefabricated tube films, contraction cracks, and appearance bubbles have been solved, and efficient production in low temperature conditions in winter is realized, and the quality and durability of pipes are improved.

CN118851622BActive Publication Date: 2025-01-24SHIJIAZHUANG CHANGAN YUCAI BUILDING MATERIALS +2
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
CN202411365201.1
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-09-29
Publication Date
2025-01-24
Estimated Expiration
2044-09-29

AI Technical Summary

Technical Problem

The prefabricated pipe sheets have low strength in the early stages, shrinkage cracks and many appearance bubbles, especially under low temperature conditions in winter, which affects production efficiency, quality and durability.

Method used

The early strength shrinkage reducing admixture for prefabricated segments is used. The admixture consists of high belite sulfoaluminate cement, lithium slag powder, grade I fly ash, polycarboxylic acid high-performance water-reducing agent powder, and low-temperature reinforcing agent. It is composed of water-retaining and slurry-extracting agent. Through the synergistic effect of these components, it can improve the early strength of concrete, reduce shrinkage cracks, and improve the appearance.

Benefits of technology

It significantly improves the early strength of prefabricated segments, shortens steam curing time, reduces energy consumption, reduces shrinkage cracks, and improves appearance quality, making it suitable for low-temperature production conditions in winter.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
  • Figure SMS_2
    Figure SMS_2
Patent Text Reader

Abstract

The invention discloses an early strength shrinkage reducing admixture for prefabricated pipe segments, a preparation method and an application thereof, and belongs to the technical field of building materials. By weight, the components of the early strength shrinkage reducing admixture for prefabricated pipe segments include: 30-40 parts of high belite sulphoaluminate cement, 30-40 parts of lithium slag powder, 5-10 parts of Class I fly ash, 0.5-1 parts of polycarboxylic acid high-performance water reducing agent powder, 20-30 parts of low-temperature enhancer and 0.1-0.3 parts of water-retaining slurry extracting agent. The early strength shrinkage reducing admixture for prefabricated pipe segments provided by the invention accelerates the hydration of cement through the synergistic effect of low-temperature enhancer, high belite sulphoaluminate cement and lithium slag powder, and can also significantly improve the early strength of concrete during the production of low-temperature pipe segments in winter, greatly shorten the steaming curing time, and reduce energy consumption. The shrinkage compensation and internal curing performance of lithium slag powder are utilized to reduce shrinkage cracks, improve the machine workability and workability of concrete through slurry extracting and water-retaining, extend the vibration time of pipe segments, and optimize the appearance of pipe segments.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of building materials, and in particular relates to an early strength shrinkage reducing admixture for prefabricated pipe segments and a preparation method and application thereof. Background Art

[0002] Prefabricated pipe segments are mainly used in underground engineering fields such as urban construction, rail transit, water conservancy projects, bridges and tunnels, and have seen strong market demand in recent years. As an important prefabricated concrete component in underground engineering construction, it must withstand external soil pressure, groundwater pressure and various dynamic load impacts, and its quality is directly related to the overall safety and stability of underground engineering. In the production process, the low early strength of prefabricated fresh concrete leads to a slow mold turnover rate, which restricts the production efficiency and economic benefits of the pipe segments. Nowadays, steam curing is widely used to improve the early strength of prefabricated concrete, but there are large investments and high energy consumption in steam curing equipment. During steam curing, shrinkage cracks often occur in the pipe segments due to water loss and temperature differences. The large amount of cementitious materials used in the pipe segment concrete leads to serious self-shrinkage, and the poor vibration resistance of the concrete causes many bubbles on the appearance of the pipe segments. Therefore, the three major difficulties in the production process of prefabricated pipe segments, namely low early strength, shrinkage cracks and many bubbles on the appearance, seriously affect the production efficiency, quality and durability of the pipe segments.

[0003] In the prior art, CN118206337A discloses a prefabricated subway segment concrete based on ultrafine powder, which improves the mechanical strength of concrete, its workability and corrosion resistance by introducing a rigid ring on the side chain of polycarboxylic acid water-reducing agent and adding highly active ultrafine powder. CN112608105A discloses a multi-dimensional reduction of the corrosion effect of chloride ions on steel bars by progressively matching waterproof coating, expansion agent, hydrotalcite and corrosion inhibitor, and has high resistance to chloride ion penetration, so that the steel bars in the prepared prefabricated segment are not easy to rust, and the durability of the prefabricated segment is improved. CN117003508A discloses an early-strength slow-release polycarboxylic acid water-reducing agent for prefabricated components, which is prepared by introducing sulfonic acid amide, terminal amino polyoxyethylene ether acrylate and reducing the main chain length. The addition of viscosity reducer and foam inhibitor can increase the slurry volume and softness of prefabricated fresh concrete, ensure the continuity of production, improve production efficiency, and enhance the early strength of concrete, so as to realize the prefabricated concrete without steaming, save costs, reduce bubbles and improve aesthetics.

[0004] At present, the problems of low early strength, shrinkage cracks and appearance bubbles of prefabricated components are often solved by designing and improving the molecular structure of polycarboxylic acid water-reducing agent and adding high-activity ultrafine powder, early strength agent, waterproof coating, etc. These measures can improve early strength, enhance durability and improve appearance to a certain extent, but there are still some problems, such as the early strength improvement is not obvious when producing low-temperature segments in winter, the shrinkage cracks are serious when using the steam curing method, which has an adverse effect on the workability of concrete, and there are many appearance bubbles, etc. Therefore, how to prepare prefabricated components with high early strength of segments at low temperatures in winter, short steam curing time, accelerated production cycle and cost saving, while compensating for shrinkage, reducing cracks, and improving appearance bubbles, is a difficult problem that urgently needs to be solved in this field. Summary of the invention

[0005] The purpose of the present invention is to provide an early strength shrinkage reducing admixture for prefabricated pipe segments, and a preparation method and application thereof. By using the early strength shrinkage reducing admixture provided by the present invention to replace part of the cement of the prefabricated pipe segment, and utilizing the synergistic effect of each component in the early strength shrinkage reducing admixture, the prefabricated pipe segment concrete has good machine workability, high early strength, short steam curing time, reduced shrinkage cracks of the prefabricated pipe segment, and reduced energy consumption.

[0006] To achieve the above object, the present invention provides the following technical solutions:

[0007] One of the technical solutions of the present invention is to provide an early strength shrinkage reducing admixture for prefabricated pipe segments, which comprises, by weight, 30-40 parts of high belite sulphoaluminate cement, 30-40 parts of lithium slag powder, 5-10 parts of Class I fly ash, 0.5-1 parts of polycarboxylic acid high-performance water reducing agent powder, 20-30 parts of low-temperature enhancer and 0.1-0.3 parts of water-retaining slurry extracting agent;

[0008] The low temperature enhancer comprises, by weight, 120-140 parts of a polycarboxylic acid high-performance dispersant, 192-208 parts of calcium nitrate, 144-160 parts of sodium silicate, 20 parts of polyethylene glycol, 10 parts of triethanolamine, 2 parts of a defoamer and 2 parts of sodium hydroxide;

[0009] The water-retaining pulping agent comprises, by weight, 78 to 80 parts of vinyl acetate, 4 to 5 parts of methanol, 1 to 2 parts of hydroxypropyl methylcellulose, 5 to 6 parts of tert-butyl perbenzoate, 0.6 to 0.8 parts of methacrylic acid, 0.3 to 0.4 parts of sodium dodecyl diphenyl ether disulfonate and 8 to 9 parts of triethanolamine.

[0010] The calcium sulfoaluminate in high-belite sulfoaluminate cement reacts quickly with calcium sulfate to form calcium sulfonate and aluminum glue, which makes the cement have the performance of rapid coagulation and hardening. It can achieve high compressive strength in a relatively short time, which helps to improve the early strength of prefabricated pipe segments and shorten the steaming time. Prefabricated pipe segments generally use a high amount of glue, and modern cement has a large fineness and severe self-shrinkage. The total amount of hydration heat release of high-belite sulfoaluminate cement is low, and it has a micro-expansion function, which compensates for shrinkage by expansion and has excellent crack resistance.

[0011] Most of the SiO in lithium slag powder 2 and Al 2 O 3 It exists in amorphous form and is the main source of lithium slag activity. 2 and Al 2 O 3 Ca(OH) produced by cement hydration 2 The volcanic ash reaction is beneficial to improve the mid- and late-stage strength of the segment concrete, reduce the permeability of the concrete, prevent the intrusion of moisture and harmful substances, and improve the durability of the segment. 4 2- The sulfur trioxide content in the form of cement is high. When the cement hydration product calcium aluminate and sulfate ions combine to form calcium sulfonate micro-expansion products, it has a compensatory effect on the shrinkage and self-shrinkage caused by humidity difference and temperature difference during the curing process of the pipe segment. At the same time, the porous structure of lithium slag powder has a large internal specific surface area and has obvious adsorption of water. It has long-term water retention and automatic water replenishment functions during the coagulation and hardening stage of the pipe segment to reduce the shrinkage and cracking problems caused by the decrease in relative humidity caused by cement hydration inside the concrete. Especially during the steam curing process, when the surface of the pipe segment loses water at high temperature, the water inside the lithium slag will be slowly released to reduce the surface temperature of the concrete and prevent cracking due to temperature changes and water loss.

[0012] Since lithium slag powder will reduce the initial fluidity of the segment concrete, the present invention utilizes the lubricating effect of the spherical particles of Class I fly ash in the concrete to improve the fluidity. At the same time, the volcanic ash effect of the fly ash can improve the mid-to-late strength of the concrete.

[0013] The porous structure of lithium slag powder has adsorption to water and water reducing agent, which will cause the problem of reduced initial fluidity of segment concrete. The present invention adds high-performance polycarboxylic acid water reducing agent powder with high water reduction and fast loss, so that the concrete has greater fluidity when loaded into the mold, which is helpful for the discharge of bubbles during the vibration process. At the same time, it is required that the concrete loses fluidity faster after half an hour, which helps to avoid the appearance of waves and early plastic cracks on the segment surface and improve the early strength.

[0014] The low-temperature enhancer of the present invention has good ultra-early strength performance, and can greatly improve the early strength of concrete under low temperature, steam curing and normal temperature conditions. Its mechanism of action is the cement hydration crystal nucleation and crystal growth stage, providing a crystal nucleus growth point for cement hydration, promoting the early generation of hydrated calcium silicate gel, and making the cement hydration enter an accelerated period. It can shorten or even eliminate the steam curing process of the pipe segment, reduce energy consumption, and improve the mold turnover rate. At the same time, the dispersant in the low-temperature early strength agent has the performance of high water loss and fast loss, which is conducive to compensating for the reduction of the initial fluidity of concrete caused by lithium slag powder, and the defoamer in the low-temperature early strength agent is conducive to eliminating the influence of large bubbles generated in the admixture on the appearance quality of the pipe segment.

[0015] The raw materials in the water-retaining slurry extracting agent of the present invention react freely to form a gel network of entangled molecular chains, which can introduce stable small bubbles into the prefabricated pipe segment concrete with a small slump, promote the uniform dispersion of the cement paste, make the paste rich and full, help to improve the machine discharge and workability of the concrete by slurry extraction, and at the same time enhance the water retention of the concrete, prolong the vibration time of the pipe segment without water seepage and segregation, thereby significantly improving the appearance of the pipe segment.

[0016] Preferably, the specific surface area of ​​the lithium slag powder is 800±50m 2 / kg,SiO 2 The content is not less than 35%, Al 2 O 3 The content is not less than 15%, SO 3 The content is 15±5%.

[0017] When the lithium slag is ground to a surface area of ​​800 ± 50 m 2 / kg, lithium slag powder has higher pozzolanic activity.

[0018] Preferably, the water reduction rate of the polycarboxylic acid high performance water reducing agent powder is greater than 40%.

[0019] Preferably, the polycarboxylic acid high-performance dispersant has a water reduction rate greater than 30% and a solid content of 50%.

[0020] Preferably, the specific surface area of ​​the low temperature enhancer is not less than 350 m 2 / kg.

[0021] Preferably, the specific surface area of ​​the water-retaining pulping agent is not less than 350 m 2 / kg.

[0022] The second technical solution of the present invention is to provide a method for preparing the above-mentioned early strength shrinkage reducing admixture for prefabricated pipe segments, the steps comprising:

[0023] A polycarboxylic acid high-performance dispersant, polyethylene glycol and water are mixed, and after stirring evenly, a defoamer and sodium hydroxide are added, and water is continued to be added until the pH value is 12±0.5; then a calcium nitrate solution with a mass concentration of 80% and a sodium silicate solution with a mass concentration of 40% are dripped in at the same time, and triethanolamine is added after the dripping is completed, and a milky white liquid is obtained after stirring, and the mixture is dried and ground to obtain a low-temperature enhancer;

[0024] Vinyl acetate, methanol, hydroxypropyl methylcellulose, tert-butyl peroxybenzoate, methacrylic acid and sodium dodecyl diphenyl ether disulfonate are sequentially added to a reaction container, stirred evenly and heated to 110±5°C, cooled after the reaction, triethanolamine is added, stirred evenly and allowed to stand, dried and ground to obtain a water-retaining pulping agent;

[0025] The early strength shrinkage reducing admixture for the prefabricated pipe segment is obtained by mixing high belite sulphoaluminate cement, lithium slag powder, Class I fly ash, polycarboxylic acid high-performance water reducing agent powder, the low-temperature enhancer and the water-retaining slurry extracting agent.

[0026] Preferably, the dripping time of the calcium nitrate solution with a mass concentration of 80% is controlled to be 4 hours; the dripping time of the sodium silicate solution with a mass concentration of 40% is controlled to be 2 hours; and the reaction time is 8 hours.

[0027] The third technical solution of the present invention is to provide an application of the above-mentioned early strength and shrinkage reducing admixture for prefabricated pipe segments in the preparation of prefabricated pipe segments.

[0028] Preferably, the early strength shrinkage reducing admixture for the prefabricated pipe segment is used to replace part of the cement in the prefabricated pipe segment.

[0029] The beneficial technical effects of the present invention are as follows:

[0030] In the present invention, the lithium slag is dried and then fully ground to stimulate the activity, and a large amount of SO in the lithium slag is used. 3 The micro-expansion produced is used to compensate for the shrinkage. The porous structure of lithium slag powder is used to absorb water as a curing agent in concrete to reduce cracking on the surface of the pipe segment. At the same time, low-temperature enhancers and high-belite sulphoaluminate cement are used to eliminate the adverse effects of lithium slag on the early strength of concrete. The early, mid-term and late strength of concrete can be greatly improved under low temperature, steam curing and room temperature conditions. Class I fly ash and polycarboxylic acid high-performance water-reducing agent powder are used to improve the initial fluidity of concrete and reduce the effect of the high water demand of lithium slag powder on the workability of concrete. Through the synergistic effect of various materials, the excellent performance of lithium slag is fully utilized, while the adverse effects brought by lithium slag are eliminated, turning low-cost and abundant industrial waste slag into treasure and realizing resource utilization.

[0031] The early strength shrinkage-reducing admixture for prefabricated pipe segments provided by the present invention accelerates the hydration of cement through the synergistic effect of low-temperature enhancer, high-belite sulphoaluminate cement and lithium slag powder, and can also significantly improve the early strength of concrete during low-temperature production in winter, greatly shorten the steam curing time, and reduce energy consumption. The shrinkage compensation and internal curing performance of lithium slag powder are utilized to reduce shrinkage cracks, improve the machine workability of concrete by slurry extraction and water retention, extend the vibration time of pipe segments, and optimize the appearance of pipe segments. DETAILED DESCRIPTION

[0032] Now, various exemplary embodiments of the present invention are described in detail, and this detailed description should not be considered as a limitation of the present invention, but should be understood as a more detailed description of certain aspects, characteristics and embodiments of the present invention. It should be understood that the terms described in the present invention are only for describing specific embodiments and are not used to limit the present invention.

[0033] In addition, for the numerical range in the present invention, it is understood that each intermediate value between the upper and lower limits of the range is also specifically disclosed. The intermediate value in any stated value or stated range, and each smaller range between any other stated value or intermediate value in the range is also included in the present invention. The upper and lower limits of these smaller ranges can be independently included or excluded in the scope.

[0034] Unless otherwise specified, all technical and scientific terms used herein have the same meaning as commonly understood by those skilled in the art to which the invention pertains. Although only preferred methods and materials are described herein, any methods and materials similar or equivalent to those described herein may also be used in the practice or testing of the present invention.

[0035] The words “include,” “including,” “have,” “contain,” etc. used in this document are open-ended terms, meaning including but not limited to.

[0036] Room temperature in the present invention refers to a temperature of 20±10°C.

[0037] The cement used in the embodiments of the present invention and the comparative examples is high-strength, fast-setting, fast-hardening, high-belite sulphoaluminate cement with a strength grade of 52.5.

[0038] The lithium slag powder used in the embodiments of the present invention and the comparative examples is obtained by drying and grinding lithium slag, and its specific surface area is 820m 2 / kg,SiO 2 The content is 45%, Al 2 O 3 The content is 24%, SO 3 The content is 16%.

[0039] The Class I fly ash used in the embodiments of the present invention and the comparative examples had a 45 μm square hole sieve residue of 4.6%, a loss on ignition of 2.6%, and SO3 The content is 1.2%.

[0040] The polycarboxylic acid high-performance water-reducing agent powder used in the examples of the present invention and the comparative examples was purchased from Shijiazhuang Changan Yucai Building Materials Co., Ltd., with a water reduction rate of 42%, high water reduction and fast loss.

[0041] The polycarboxylic acid high-performance dispersant in the raw materials of the low-temperature enhancer used in the embodiments of the present invention and the comparative examples is a polycarboxylic acid high-performance dispersant 114 product produced by Shijiazhuang Changan Yucai Building Materials Co., Ltd., with a water reduction rate of 32%, high water reduction and fast loss, and a solid content of 50%; the molecular weight of polyethylene glycol is 20,000.

[0042] Unless otherwise specified, the "parts" mentioned in the examples and comparative examples of the present invention refer to parts by weight.

[0043] Example 1

[0044] Preparation of early strength shrinkage reducing admixture for prefabricated segments:

[0045] (1) Preparation of low temperature enhancer

[0046] 120 parts of polycarboxylic acid high-performance dispersant, 20 parts of polyethylene glycol and 300 parts of deionized water were added to the reactor, the stirrer speed was set to 500 rpm, and the mixture was stirred for 30 minutes to be fully mixed, and then 2 parts of defoamer and 2 parts of sodium hydroxide were added, and water was continued to be added until the pH value was 12 to obtain a mixed solution;

[0047] The speed of the stirrer in the reactor was adjusted to 3000 rpm, and 240 parts of 80% calcium nitrate solution (equivalent to 192 parts of calcium nitrate) and 360 parts of 40% sodium silicate solution (equivalent to 144 parts of sodium silicate) were simultaneously dripped into the mixed solution. The dripping time of the calcium nitrate solution was controlled within 4 hours, and the dripping time of the sodium silicate solution was controlled within 2 hours.

[0048] After the calcium nitrate solution was added dropwise, 10 parts of triethanolamine was added and stirred for 30 minutes to obtain a milky white liquid, which was dried and ground for 10 minutes to obtain a low-temperature enhancer (specific surface area of ​​395m 2 / kg).

[0049] (2) Preparation of water-retaining pulping agent

[0050] 80 parts of vinyl acetate, 4 parts of methanol, 2 parts of hydroxypropyl methylcellulose, 5 parts of tert-butyl perbenzoate, 0.7 parts of methacrylic acid and 0.3 parts of sodium dodecyl diphenyl ether disulfonate were added to the reactor in sequence, stirred evenly and heated to 110°C. After reacting for 8 hours, the mixture was cooled to room temperature, 8 parts of triethanolamine was added, stirred for 30 minutes, and then allowed to stand for 2 hours, dried, and ground for 10 minutes to obtain a water-retaining pulping agent (with a specific surface area of ​​375m2 / kg).

[0051] (3) 40 parts of high-strength, fast-setting, fast-hardening high-belite sulphoaluminate cement, 30 parts of lithium slag powder, 5.3 parts of Class I fly ash, 0.5 parts of polycarboxylic acid high-performance water-reducing agent powder, 24 parts of the low-temperature enhancer prepared in step (1) and 0.2 parts of the water-retaining slurry extracting agent prepared in step (2) are mixed and stirred evenly to prepare an early strength shrinkage-reducing admixture for prefabricated pipe segments.

[0052] Example 2

[0053] Preparation of early strength shrinkage reducing admixture for prefabricated segments:

[0054] Compared with Example 1, the only difference is that the proportions of the raw materials in step (3) are: 30 parts of high-strength, fast-setting and fast-hardening high-belite sulphoaluminate cement, 40 parts of lithium slag powder, 8.9 parts of Class I fly ash, 1 part of polycarboxylic acid high-performance water-reducing agent powder, 20 parts of low-temperature enhancer and 0.1 parts of water-retaining slurry extracting agent.

[0055] Example 3

[0056] Preparation of early strength shrinkage reducing admixture for prefabricated segments:

[0057] Compared with Example 1, the only difference is that the proportions of the raw materials in step (3) are: 30 parts of high-strength, fast-setting and fast-hardening high-belite sulphoaluminate cement, 34 parts of lithium slag powder, 5.4 parts of Class I fly ash, 0.5 parts of polycarboxylic acid high-performance water-reducing agent powder, 30 parts of low-temperature enhancer and 0.1 parts of water-retaining slurry extracting agent.

[0058] Example 4

[0059] Preparation of early strength shrinkage reducing admixture for prefabricated segments:

[0060] Compared with Example 2, the only difference is that in the preparation process of the low-temperature enhancer in step (1), the polycarboxylic acid high-performance dispersant is 140 parts, the polyethylene glycol is 20 parts, the defoamer is 2 parts, the sodium hydroxide is 2 parts, the calcium nitrate solution with a mass concentration of 80% is 260 parts (equivalent to 208 parts of calcium nitrate), the sodium silicate solution with a mass concentration of 40% is 400 parts (equivalent to 160 parts of sodium silicate), and triethanolamine is 10 parts. The specific surface area of ​​the prepared low-temperature enhancer is 405m 2 / kg.

[0061] Example 5

[0062] Preparation of early strength shrinkage reducing admixture for prefabricated segments:

[0063] Compared with Example 3, the only difference is that in the preparation process of the low-temperature enhancer in step (1), the polycarboxylic acid high-performance dispersant is 130 parts, the polyethylene glycol is 20 parts, the defoamer is 2 parts, the sodium hydroxide is 2 parts, the calcium nitrate solution with a mass concentration of 80% is 250 parts (equivalent to 200 parts of calcium nitrate), the sodium silicate solution with a mass concentration of 40% is 380 parts (equivalent to 152 parts of sodium silicate), and triethanolamine is 10 parts. The specific surface area of ​​the prepared low-temperature enhancer is 385m 2 / kg.

[0064] Comparative Example 1

[0065] Preparation of early strength shrinkage reducing admixture for prefabricated segments:

[0066] Compared with Example 1, the only difference is that the lithium slag powder is only ground to a specific surface area of ​​510m 2 / kg.

[0067] Comparative Example 2

[0068] Preparation of early strength shrinkage reducing admixture for prefabricated segments:

[0069] Compared with Example 1, the only difference is that the amount of the low temperature enhancer is reduced from 24 parts to 8.8 parts.

[0070] Comparative Example 3

[0071] Preparation of early strength shrinkage reducing admixture for prefabricated segments:

[0072] Compared with Example 1, the only difference is that in the preparation process of the low-temperature enhancer, the amount of the polycarboxylic acid high-performance dispersant is reduced from 120 parts to 80 parts.

[0073] Comparative Example 4

[0074] Preparation of early strength shrinkage reducing admixture for prefabricated segments:

[0075] Compared with Example 1, the only difference is that during the preparation of the low-temperature enhancer, when the calcium nitrate solution and the sodium silicate solution are added dropwise, the speed of the stirrer in the reaction kettle is reduced from 3000 rpm to 1500 rpm.

[0076] Comparative Example 5

[0077] Preparation of early strength shrinkage reducing admixture for prefabricated segments:

[0078] Compared with Example 1, the only difference is that the addition of the water-retaining pulping agent is omitted.

[0079] Effect verification:

[0080] The performance of the early strength shrinkage reducing admixtures for prefabricated pipe segments prepared in Examples 1-5 and Comparative Examples 1-4 was tested through indoor concrete tests.

[0081] In the indoor concrete test, the early strength and shrinkage reducing admixtures for prefabricated pipe segments prepared in Examples 1-5 and Comparative Examples 1-4 were used to replace 15wt.% of cement in the concrete (the benchmark group was not replaced), wherein the component ratio of the concrete was: the mass ratio of cement, fly ash, machine-made sand, crushed stone, water, and admixture was 400:40:757:1135:132:4.18. The cement was P·O 52.5, produced by China Resources Cement Co., Ltd.; the fly ash was Grade I, produced by Foshan Hengyi Environmental Protection Building Materials Co., Ltd.; the machine-made sand and crushed stone were purchased from the market, the machine-made sand was medium sand, the fineness modulus was 2.6, and the methylene blue value was 1.0; the crushed stone was well graded, the particle size was 5-20mm, the needle-like content was less than 5.0%, and the mud content was less than 0.5%. According to the standard "Standard for Test Methods of Ordinary Concrete Mixture Performance" GB / T 50080-2016 and "Standard for Test Methods of Physical and Mechanical Properties of Concrete" GB / T 50081-2019, after preparing the standard test blocks, they were placed in a constant temperature room at a low temperature of 5°C for 2 hours, and then the test blocks of the reference group were placed in a steam curing box at 50°C for 6 hours. The test blocks of Examples 1-5 and Comparative Examples 1-4 were placed in a constant temperature room at 5°C for 3 hours, and then placed in a steam curing box at 50°C for 3 hours to measure the compressive strength. According to the standard "Standard for Test Methods of Long-term Performance and Durability of Ordinary Concrete" GB / T 50082-2009, a horizontal concrete shrinkage instrument was used to measure the shrinkage of concrete. Since the shrinkage rate of concrete changed little after 90 days, the 90d shrinkage value was measured as the ultimate shrinkage value of concrete. The measurement results are shown in Table 1.

[0082] Table 1 Indoor test results of the performance of early strength and shrinkage reducing admixtures for prefabricated segments

[0083]

[0084] It can be seen from Table 1 that after replacing 15wt.% of cement with early strength shrinkage-reducing admixture in the embodiment and comparative example groups, the compressive strength after low temperature curing for 3h and high temperature steam curing for 3h is significantly higher than the compressive strength of the benchmark group after high temperature steam curing for 6h, and is much greater than the demoulding strength of 15MPa. It can be seen that after adding early strength shrinkage-reducing admixture, the steam curing time can be shortened by at least half, and the 90d shrinkage rate is significantly reduced. Comparing Example 1 with Comparative Example 1, it is shown that the appropriate lithium slag specific surface area is conducive to the improvement of the early strength of concrete. Comparing Example 1 with Comparative Example 2, the dosage of low temperature enhancer has a significant effect on the early strength of concrete. Comparing Example 1 with Comparative Example 3 and Comparative Example 4, the dispersant dosage of the low temperature enhancer and the stirring speed during the reaction process have a significant effect on the performance of the low temperature enhancer.

[0085] The performance of the early strength and shrinkage reducing admixtures for prefabricated pipe segments prepared in Example 1 and Comparative Example 5 were tested through actual engineering pipe segment production applications.

[0086] Example 1 and Comparative Example 5 were actually used for segment production at low temperatures in winter. The prefabricated segments prepared in Example 1 and Comparative Example 5 used early strength shrinkage reducing admixtures to replace 15 wt.% of cement in concrete (the benchmark group did not make any replacement). The component ratio of concrete was determined by referring to the above-mentioned indoor concrete test. The vibration time was determined according to the bubble escape situation and the thickness of the floating slurry. The surface cracks and external bubbles of the segments were observed and collected. The statistical results are shown in Table 2.

[0087] Table 2 Appearance of early strength and shrinkage reducing admixtures used in segment production

[0088]

[0089] It can be seen from Table 2 that after adding the early strength shrinkage-reducing admixture, the shrinkage cracks disappeared, mainly because the micro-expansion of the lithium slag powder compensated for the shrinkage and the curing function during the coagulation and hardening stage, which reduced the cracking problem caused by the shrinkage of the concrete due to temperature difference, humidity difference and self-shrinkage. By comparing Example 1 with Comparative Example 5, it can be seen that the water-retaining slurry extracting agent can extend the vibration time of the pipe segment, and there is no excessively thick slurry on the surface of the pipe segment to cause shrinkage cracks, which is conducive to the discharge of bubbles. There are only a small number of small bubbles in the water-stop grooves on both sides, and the appearance is significantly improved.

[0090] The embodiments described above are only descriptions of the preferred modes of the present invention, and are not intended to limit the scope of the present invention. Without departing from the design spirit of the present invention, various modifications and improvements made to the technical solutions of the present invention by ordinary technicians in this field should all fall within the protection scope determined by the claims of the present invention.

Claims

1. An early strength shrinkage reducing admixture for prefabricated pipe segments, characterized in that: The components include, by weight: 30-40 parts of high-belite sulphoaluminate cement, 30-40 parts of lithium slag powder, 5-10 parts of Class I fly ash, 0.5-1 parts of polycarboxylic acid high-performance water-reducing agent powder, 20-30 parts of low-temperature enhancer and 0.1-0.3 parts of water-retaining slurry-raising agent; The low temperature enhancer comprises, by weight, 120-140 parts of a polycarboxylic acid high-performance dispersant, 192-208 parts of calcium nitrate, 144-160 parts of sodium silicate, 20 parts of polyethylene glycol, 10 parts of triethanolamine, 2 parts of a defoamer and 2 parts of sodium hydroxide; The water-retaining pulping agent comprises, by weight, 78 to 80 parts of vinyl acetate, 4 to 5 parts of methanol, 1 to 2 parts of hydroxypropyl methylcellulose, 5 to 6 parts of tert-butyl perbenzoate, 0.6 to 0.8 parts of methacrylic acid, 0.3 to 0.4 parts of sodium dodecyl diphenyl ether disulfonate and 8 to 9 parts of triethanolamine; The preparation steps of the early strength shrinkage reducing admixture for prefabricated pipe segments include: A polycarboxylic acid high-performance dispersant, polyethylene glycol and water are mixed, and after stirring evenly, a defoamer and sodium hydroxide are added, and water is continued to be added until the pH value is 12±0.5; then a calcium nitrate solution with a mass concentration of 80% and a sodium silicate solution with a mass concentration of 40% are dripped in at the same time, and triethanolamine is added after the dripping is completed, and a milky white liquid is obtained after stirring, and the mixture is dried and ground to obtain a low-temperature enhancer; Vinyl acetate, methanol, hydroxypropyl methylcellulose, tert-butyl peroxybenzoate, methacrylic acid and sodium dodecyl diphenyl ether disulfonate are sequentially added to a reaction container, stirred evenly and heated to 110±5°C, cooled after the reaction, triethanolamine is added, stirred evenly and allowed to stand, dried and ground to obtain a water-retaining pulping agent; The early strength shrinkage reducing admixture for the prefabricated pipe segment is obtained by mixing high belite sulphoaluminate cement, lithium slag powder, Class I fly ash, polycarboxylic acid high-performance water reducing agent powder, the low-temperature enhancer and the water-retaining slurry extracting agent.

2. The early strength shrinkage reducing admixture for prefabricated pipe segments according to claim 1, characterized in that: The specific surface area of ​​the lithium slag powder is 800±50m 2 / kg, SiO2 content is not less than 35%, Al2O3 content is not less than 15%, and SO3 content is 15±5%.

3. The early strength shrinkage reducing admixture for prefabricated pipe segments according to claim 1, characterized in that: The water reduction rate of polycarboxylic acid high performance water reducing agent powder is greater than 40%.

4. The early strength shrinkage reducing admixture for prefabricated pipe segments according to claim 1, characterized in that: The polycarboxylic acid high-performance dispersant has a water reduction rate of greater than 30% and a solid content of 50%.

5. The early strength shrinkage reducing admixture for prefabricated pipe segments according to claim 1, characterized in that: The specific surface area of ​​the low temperature enhancer is not less than 350m 2 / kg.

6. The early strength shrinkage reducing admixture for prefabricated pipe segments according to claim 1, characterized in that: The specific surface area of ​​the water-retaining pulping agent is not less than 350m 2 / kg.

7. A method for preparing the early strength and shrinkage reducing admixture for prefabricated pipe segments according to any one of claims 1 to 6, characterized in that the steps include: A polycarboxylic acid high-performance dispersant, polyethylene glycol and water are mixed, and after stirring evenly, a defoamer and sodium hydroxide are added, and water is continued to be added until the pH value is 12±0.5; then a calcium nitrate solution with a mass concentration of 80% and a sodium silicate solution with a mass concentration of 40% are dripped in at the same time, and triethanolamine is added after the dripping is completed, and a milky white liquid is obtained after stirring, and the mixture is dried and ground to obtain a low-temperature enhancer; Vinyl acetate, methanol, hydroxypropyl methylcellulose, tert-butyl peroxybenzoate, methacrylic acid and sodium dodecyl diphenyl ether disulfonate are sequentially added to a reaction container, stirred evenly and heated to 110±5°C, cooled after the reaction, triethanolamine is added, stirred evenly and allowed to stand, dried and ground to obtain a water-retaining pulping agent; The early strength shrinkage reducing admixture for the prefabricated pipe segment is obtained by mixing high belite sulphoaluminate cement, lithium slag powder, Class I fly ash, polycarboxylic acid high-performance water reducing agent powder, the low-temperature enhancer and the water-retaining slurry extracting agent.

8. The preparation method according to claim 7, characterized in that: The dripping time of the calcium nitrate solution with a mass concentration of 80% is controlled to be 4 hours; the dripping time of the sodium silicate solution with a mass concentration of 40% is controlled to be 2 hours; and the reaction time is 8 hours.

9. Use of the early strength and shrinkage reducing admixture for prefabricated pipe segments according to any one of claims 1 to 6 in the preparation of prefabricated pipe segments.

10. The use according to claim 9, characterized in that: The early strength shrinkage reducing admixture for the prefabricated pipe segment is used to replace part of the cement in the prefabricated pipe segment.

Citation Information

Patent Citations

  • Prefabricated segment concrete and prefabricated segment

    CN112608105A

  • Polycarboxylate superplasticizer for prefabricated part, concrete and preparation method of concrete

    CN117003508A

  • Blending material for high-early-strength concrete

    CN101508557A

  • Reinforced concrete admixture and preparation method thereof

    CN112851187A